Remittances and the effectiveness of foreign aid - Minasyan, Anna; Nunnenkamp, Peter (Review of development economics, 2016)
Abstract We argue that donors could improve the effectiveness of foreign aid by pursuing complementary and coherent non-aid policies. In particular, we hypothesize that aid has stronger growth effects if recipients receive more aid from donors who allow for (temporary) worker mobility and (more permanent) migration. We focus on overall remittances paid by the donor countries to proxy for worker mobility and migration. Our empirical results support the hypothesis that higher remittances paid by donor countries strengthen the growth effects of foreign aid.